Maurice Samuel : life and letters of a secular Jewish contrarian - Levenson, Alan T. (The University of Alabama Press, 2022)
"This short intellectual biography reassesses one of the premier Jewish humanists of the mid-twentieth century, the Rumanian-born, English-educated, American belletrist Maurice Samuel. Although he spoke in a staccato Midlands accent, Samuel left Manchester, England in 1913, joined the American Army, served in military intelligence in World War I, and became a United States citizen. Samuel resettled his family in Palestine in 1929, then returned to the US, and spent his most creative years in New York City. A diaspora intellectual, or "rootless cosmopolitan," as Alan Levenson describes him, Samuel made an indelible mark on many features of contemporary Jewish thought and culture"-- Provided by publisher.
Keywords: Samuel, Maurice, -- 1895-1972.; Samuel, Maurice, -- 1895-1972; Jews, Romanian -- New York (State) -- New York -- Biography.; Yiddish literature -- History and criticism.; Jewish authors -- New York (State) -- New York -- Biography.; Zionists -- New York (State) -- New York -- Biography.; Judaism -- 20th century.; Jewish learning and scholarship.; New York (N.Y.) -- Biography.; Littérature yiddish -- Histoire et critique.; Écrivains juifs -- New York (État) -- New York -- Biographies.; Judaïsme -- Histoire -- 20e siècle.; Juifs -- Savoir et érudition.; Juifs roumains -- New York (État) -- New York -- Biographies.; Jewish.; HISTORY.; Judaism.; RELIGION.; Zionists; Yiddish literature; Judaism; Jews, Romanian; Jewish learning and scholarship; Jewish authors; New York (State) -- New York; 1900-1999; Criticism, interpretation, etc.; Biographies